Prospective analysis of ventilated patients in the Paediatric Medical Intensive Care Unit of Lady Ridgeway Hospital - Thadchanamoorthy, V.; de Silva, S.; Sarathchandra, J.; Kumarendran, B. (Sri Lanka College of Paediatricians, 2012)
OBJECTIVE: To determine the characteristics and outcome of ventilated patients in the paediatric medical intensive care unit (PICU) of Lady Ridgeway Hospital for Children (LRH), Colombo. DESIGN: Prospective descriptive study METHOD: The study population consisted of all ventilated paediatric patients admitted to PICU, LRH from 1st March to 31st August, 2009. The factors studied included demographic profile (age, sex, residence, transfer), length of stay on ventilator, indication for ventilation, details of organ dysfunction and the final outcome. RESULTS: There were 152 patients ventilated over the study period of six months. Seventy three were under one year of age. Male to female ratio was 1.17:1. A significant proportion (n=105) were from the Western province. Eighty five patients were transferred from medical wards of LRH. Median duration of ventilation was six days (IRQ 4-10). Indications for ventilation included respiratory problems (85), neurological disorders (13), cardiac causes (5), hepatic problem (1) and miscellaneous diseases (48) including 32 from dengue syndromes. There were 42 deaths among ventilated patients giving an overall mortality rate of 27.6%. Multi-organ dysfunction syndrome (MODS) on admission accounted for 81% of the deaths. Bronchopneumonia (16) and dengue haemorrhagic fever (12) were the main underlying causes of death. Thirty two (21%) had anaemia while in the PICU, 15 of them having anaemia on admission. Nosocomial infection was present in 17 (11%) patients. Children transferred from other provinces had a higher risk of death than those from the Western province (OR=1.5, 95% CI: 0.7 – 3.3). CONCLUSIONS: MODS on admission accounted for 81% of the deaths. Bronchopneumonia and dengue haemorrhagic fever were the main underlying causes of death. Children transferred from other provinces had a higher risk of death compared to those from the Western province
Indexed in Scopus